Tissue print of prostate biopsy: a novel tool in the diagnostic procedure of prostate cancer - Vicentini Carlo; Sanità Patrizia; Pace Gianna; Angelucci Adriano; Bologna Mauro (BMC, 2011)
Abstract Background Nowadays, the histological examination of prostate core needle biopsies is still regarded as the gold standard in the diagnosis of prostate cancer (PCa). We investigated if the tissue print of core needle biopsy (biopsy print) could be used as adjunctive molecular investigative procedures in conjunction with routine histological examination of biopsy to improve PCa diagnosis. Methods The direct contact of PCa core biopsy to nitrocellulose membrane resulted in the release of a cellular micropeel that was used for downstream analytical procedures. Results By zymogram print-phoresis we demonstrated that matrix metalloproteases MMP-2 and MMP-9 could be visualized in biopsy prints and that the gelatinolytic activity was positively correlated with immunohistochemistry analysis of the same markers in matched bioptic specimens. Moreover, we compared the ability to detect the PCa-associated hypermethylation of GSTP1 promoter in DNA extracted from biopsy prints with those of the corresponding core needle biopsies. Biopsy prints demonstrated the same specificity of biopsies in detecting PCa (50%) while the sensitivity and the positive predictive value were lower than biopsies (56% vs 78% and 63% vs 70%, respectively). Conclusions Biopsy print, combining a molecular point of view to the routinely hystopathological analysis of prostate biopsies, should be a useful tool to improve the diagnosis of PCa.